Motivasi Belajar Siswa Melalui Penggunaan Media Audio -Visual pada Mata Pelajaran Geografi dii SMA Lokon St. Nikolaus Tomohon - Kapoh, Vidi Feronika; Lobja, Xaverius Erick; Korompis, Manuel Estefanus; Karwur, Hermon Maurits; Poli, Ellen Eva; Nugroho, Cahyadi; Nismawati, Nismawati (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
The purpose of this research is to determine the learning motivation of 10th grade social science students through the use of audio-visual media in geography subjects at Lokon St. Nikolaus Tomohon Senior High School. This research uses a qualitative method. The data collection techniques include observation, interviews, and documentation studies. The data analysis techniques follow the interactive models of Miles and Huberman, including data collection, data reduction, data presentation, and drawing conclusions. The conclusion of this research indicate that through the use of audiovisual media in learning, every student at Lokon St. Nikolaus Tomohon Senior High School shows motivation in the learning process for geography subjects.